Can Neutrino Self-interactions Save Sterile Neutrino Dark Matter? - Rui An; Vera Gluscevic; Ethan O. Nadler; Yue Zhang (The Astrophysical Journal Letters, 2023)
Sterile neutrinos only interact with the standard model through the neutrino sector, and thus represent a simple dark matter (DM) candidate with many potential astrophysical and cosmological signatures. Recently, sterile neutrinos produced through self-interactions of active neutrinos have received attention as a particle candidate that can yield the entire observed DM relic abundance without violating the most stringent constraints from X-ray observations. We examine consistency of this production mechanism with the abundance of small-scale structure in the universe, as captured by the population of ultrafaint dwarf galaxies orbiting the Milky Way, and derive a lower bound on the sterile-neutrino particle mass of 37 keV. Combining these results with previous collider and X-ray limits excludes 100% sterile-neutrino DM produced by strong neutrino self-coupling, mediated by a heavy (≳1 GeV) scalar; however, data permits sterile-neutrino DM production via a light mediator.